(untitled) (Conferencea, 2024)
Today, there are all opportunities for the wide development of the school of translation into and from Uzbek, and most importantly, there are no difficulties in acquiring original works of art. At the same time, the publication of language dictionaries is developing rapidly in Uzbekistan, which is a convenient opportunity for transleology.